THERMAL TRANSPORT BY HEAT PULSE PROPAGATION ON HSX: MOTIVATION, SIMULATION, AND EXPERIMENTAL PREPARATION - Weir, Gavin (My University, 2011)
Heat and particle losses in magnetically confined fusion devices are dominated by anomalous losses that are thought to be driven by micro-turbulence. Micro-turbulence contributes to the inverse cascade of energy from small-scale fluctuations to large-scale turbulent eddies, which serves to increase the level of particle and thermal loss observed in experiments. The transport of heat and particles from fusion devices is one of the greatest hurdles to magnetically confined fusion as an energy source, and understanding anomalous transport would contribute significantly to developing a fusion reactor. Transport in plasma physics is commonly characterized as classical/neoclassical or anomalous. Classical diffusive transport is an irreducible floor to transport caused by collisions in homogeneous fields, and neoclassical transport is the enhancement over classical transport by magnetic field inhomogeneity. Anomalous transport is the transport not described by neoclassical theory. The sourcing of fuel and the removal of impurities in a fusion reactor depends on particle transport, while the size of the reactor is primarily driven by thermal transport making accurate predictions of transport necessary for fusion experiments. There are two fusion experiments under construction in Europe that will be greatly affected by anomalous transport: ITER and W7-X. These two experiments are thought to be the intermediary step necessary for a demonstration fusion reactor of their respective configurations. ITER represents the tokamak configuration, and W7-X represents an optimized stellarator configuration. These two forms of magnetic confinement devices are differentiated by their confining magnetic field. Each is topologically a torus, but the confining magnetic field of the tokamak is partially generated by an inductively driven current, while the confining field of the stellarator is entirely generated by external coils. Transport in each configuration is dominated by anomalous transport, but their fundamental differences allow that transport to be studied. Heat pulse propagation experiments can be used to measure thermal transport. 1D simulations of modulated heating and the resulting heat pulses have been completed for the Helically Symmetric eXperiment (HSX). A spatially localized, modulated plasma heating source and an electron temperature diagnostic with sufficient temporal resolution are necessary to perform heat pulse propagation experiments. Simulation results are reported in Chapter 2, and the interpretation of heat pulse propagation simulations is described in Sections 2.1 and 2.1.2. The installation of a modulatable Electron Cyclotron Resonant Heating (ECRH) system is described in Section 3.1, and the upgrade and analysis of the Electron Cyclotron Emission (ECE) diagnostic on HSX is described in Sections 3.2 and 3.3.